Possibilities for enhancing permeability from VET to HE by using the VQTS model. - Luomi-Messerer, Karin [Verfasser] (My University, 2008)
"Recognising prior learning in order to enhance permeability between vocational education and training (VET) and higher education (HE) is included in European-wide educational policies and high on the official agenda in many European countries. The introduction of accreditation of prior learning (APL) is seen as an attempt a) to create new paths in education and training and, in particular, a more flexible transition between VET and HE, b) to reduce redundancies on the interface between VET and HE and c) to shorten the duration of learning in HE. In this paper, some examples of accreditation of vocational learning outcomes in HE in Austria will be presented before introducing an instrument, the VQTS model. The introduction of the VQTS model, a method for transparently describing learning outcomes, will be followed by an outline of how this approach can also be used in the context of APL to enhance permeability from VET to HE." (ÖIBF, BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Anrechnung von Bildungsleistungen; Hochschulzugang; Österreich